Genomic Landscape Reveals Chromosomally-Mediated Antimicrobial Resistome and Virulome of a High-Risk International Clone II Acinetobacter baumannii AB073 from Thailand - Rattiya Cheewapat; Jadsadaporn Redkimned; Sirikran Lekuthai; Thawatchai Kitti; Kannipa Tasanapak; Aunchalee Thanwisai; Sutthirat Sitthisak; Thanet Sornda; Hathaichanok Impheng; Sudarat Onsurathum; Udomluk Leungtongkam; Supaporn Lamlertthon; et al. (Global Health, Epidemiology and Genomics)
This study utilized integrative bioinformatics’ tools together with phenotypic assays to understand the whole-genome features of a carbapenem-resistant international clone II Acinetobacter baumannii AB073. Overall, we found the isolate to be resistant to seven antibiotic classes, penicillins, β-lactam/β-lactamase inhibitor combinations, cephalosporins, carbapenems, aminoglycosides, fluoroquinolones, and folate pathway antagonists. These resistance phenotypes are related to various chromosomal-located antibiotic resistance determinants involved in different mechanisms such as reduced permeability, antibiotic target protection, antibiotic target alteration, antibiotic inactivation, and antibiotic efflux. IC2 A. baumannii AB073 could not transfer antibiotic resistance by conjugation experiments. Likewise, mobilome analysis found that AB073 did not carry genetic determinants involving horizontal gene transfer. Moreover, this isolate also carried multiple genes associated with the ability of iron uptake, biofilm formation, immune invasion, virulence regulations, and serum resistance. In addition, the genomic epidemiological study showed that AB073-like strains were successful pathogens widespread in various geographic locations and clinical sources. In conclusion, the comprehensive analysis demonstrated that AB073 contained multiple genomic determinants which were important characteristics to classify this isolate as a successful international clone II obtained from Thailand.